Case Report: Successful Management of a 29-Day-Old Infant With Severe Hyperlipidemia From a Novel Homozygous Variant of GPIHBP1 Gene - Liu, Shu; Wang, Zhiqing; Zheng, Xianhua; Zhang, Ye; Wei, Sisi; OuYang, Haimei; Liang, Jinqun; Chen, Nuan; Zeng, Weihong; Jiang, Jianhui (Frontiers in Pediatrics, 2022)
Background: Severe hyperlipidemia is characterized by markedly elevated blood triglyceride levels and severe early-onset cardiovascular diseases, pancreatitis, pancreatic necrosis or persistent multiple organ failure if left untreated. It is a rare autosomal recessive metabolic disorder originated from the variants of lipoprotein lipase gene, and previous studies have demonstrated that most cases with severe hyperlipidemia are closely related to the variants of some key genes for lipolysis, such as LPL, APOC2, APOA5, LMF1 and GPIHBP1. Meanwhile, other unidentified causes also exist and are equally worthy of attention. Methods: The 29-day-old infant was diagnosed with severe hyperlipidemia, registering a plasma triglyceride level as high as 25.46 mmol/L. Whole exome sequencing was conducted to explore the possible pathogenic gene variants for this patient. Results: The infant was put on a low-fat diet combined with pharmacological therapy, which was successful in restraining the level of serum triglyceride and total cholesterol to a low to medium range during the follow-ups. The patient was found to be a rare novel homozygous duplication variant-c.45_48dupGCGG (Pro17Alafs*22) in GPIHBP1 gene-leading to a frameshift which failed to form the canonical termination codon TGA. The mutant messenger RNA should presumably produce a peptide consisting of 16 amino acids at the N-terminus, with 21 novel amino acids on the heels of the wild-type protein. Conclusions: Our study expands on the spectrum of GPIHBP1 variants and contributes to a more comprehensive understanding of the genetic diagnosis, genetic counseling, and multimodality therapy of families with severe hyperlipidemia. Our experience gained in this study is also contributory to a deeper insight into severe hyperlipidemia and highlights the importance of molecular genetic tests.